Living Hadith: Companion for the Dead Traditions of the Tamansari Wuluhan Village Community - Aini, Siti Qurrotul; Al-Hanifah, Hilyatul Azhar (Nur Science Institute, 2023)
Sandingan is a tradition carried out by the people of Tamansari Village when someone dies. Pairing is serving food with prayers specifically for the deceased and then giving it to the closest neighbors. The focus of study in this research is how to carry out the complementary tradition, the meaning of society regarding tradition and based on hadith and tradition analysis based on Peter Berger's social construction theory. The method used is a qualitative method with a phenomenological approach. The results of this study are that the community's meaning of the sanding tradition is carried out as a form of respect, concern and a medium of communication for people who are still alive to people who have died. In addition, their practice is based on the hadith of the Prophet Muhammad SAW. regarding the recommendation to give alms to the deceased. By using three concepts of social construction theory, Peter Beger shows that: a) externalization of the occurrence of tradition is seen by the existence of a religious text as the basis of the hadith of the Prophet Muhammad. b) objectivation can be seen in the people's belief about the meaning of the tradition of sanding as a form of respect, concern for grave experts by sending prayers and alms through the presence of sanding. c) internalization occurs through primary socialization of elders or elders and religious leaders, and secondary can be obtained through the influence of the surrounding environment.